The effect of perceived facial resemblance on parent-child relationship. (1st October 2017) - Yu, Quanlei; Zhang, Qiuying; Jin, Shenghua; Chen, Jianwen; Shi, Yaxin; Li, Yingying
Abstract: This study explored the effect of parent–child facial resemblance on the parent–child relationship in a traditional patriarchal cultural context in China. We analyzed 177 elementary and secondary school students in China. This study found that the father's perceived facial resemblance with the child significantly affected his relationship with the child. However, this result was not found among mothers. In addition, from a perspective of offspring, the sons' perceived facial resemblance with the father significantly predicted his relationship with the father, but this did not apply to daughters. Finally, this study found a mediating of father-child closeness on the relationship between perceived father-child facial resemblances and mother-child closeness. These findings enriched the theory of parental investment and extended the current model of the parent–child relationship. Highlights: Father-child facial resemblance (FCFR) significantly predicted father-child relationship. Mother-child facial resemblance did not predict mother-child relationship. Child gender moderated the effect of FCFR on the father-child relationship. Father-child closeness mediated the effect of FCFR on mother-child relationship.